Assessing Depth Perception in VR and Video See-Through AR: A Comparison on Distance Judgment, Performance, and Preference - Westermeier, Franziska; Brubach, Larissa; Wienrich, Carolin; Latoschik, Marc Erich (IEEE transactions on visualization and computer graphics, 2024)
Spatial User Interfaces along the Reality-Virtuality continuum heavily depend on accurate depth perception. However, current display technologies still exhibit shortcomings in the simulation of accurate depth cues, and these shortcomings also vary between Virtual or Augmented Reality (VR, AR: eXtended Reality (XR) for short). This article compares depth perception between VR and Video See-Through (VST) AR. We developed a digital twin of an existing office room where users had top erform five depth-dependent tasks in VR and VST AR. Thirty-two participants took part in a user study using a 1 × 4 within-subjects design. Our results reveal higher misjudgment rates in VST AR due to conflicting depth cues between virtual and physical content. Increased head movements observed in participants were interpreted as a compensatory response to these conflicting cues. Furthermore, a longer task completion time in the VST AR condition indicates a lower task performance in VST AR. Interestingly, while participants rated the VR condition as easier and contrary to the increased misjudgments and lower performance with the VST AR display, a majority still expressed a preference for the VST AR experience. We discuss and explain these findings with the high visual dominance and referential power of the physical content in the VST AR condition, leading to a higher spatial presence and plausibility.